Study on damage anisotropy and energy evolution mechanism of jointed rock mass based on energy dissipation theory - Yan, Bingqian; Kang, Hongpu; Zuo, Jianping; Wang, Peitao; Li, Xiangshang; Cai, Meifeng; Liu, Jianzhong (Bulletin of engineering geology and the environment, 2023)
The rapid development of roads and scenic spots in the suburbs of Beijing has formed a large number of artificial slopes, creating conditions for geological disasters such as collapse. It is urgent to study the influence of joint development and rainfall on the energy evolution mechanism in the process of geological disasters and rock mass failure. The deformation and failure process of jointed rock mass was accompanied by the accumulation and release of energy. To explore the damage anisotropy characteristics and the energy evolution law of jointed rock mass, nuclear magnetic resonance (NMR), triaxial compression, and acoustic emission (AE) tests of rock specimens were carried out. The pore evolution law of jointed rock specimen was analyzed, and the variation law of mechanical parameters and acoustic emission of rock specimen was studied. By establishing the energy evolution constitutive model of jointed rock specimens, the variation laws of total energy, elastic strain energy, and dissipative energy during deformation and failure of jointed rock masses were analyzed, and the energy evolution mechanism during damage and failure of jointed rock masses was revealed. The failure mode characteristics of jointed rock specimens with different dip angles under different confining pressures were analyzed.